Students’ perceptions of the rules and restrictions of gender at school: A psychometric evaluation of the Gender Climate Scale (GCS) - Ullman, Jacqueline; Hobby, Lucy; Magson, Natasha R.; Zhong, Hua Flora (Frontiers in Psychology, 2023)
Research in the field of gender and sexuality diversity and, more specifically, negative attitudes towards gender and sexuality diverse individuals, has acknowledged the relationship between individuals’ endorsement of sex-differentiated, normative gender roles and their attitudes towards gender and sexuality diversity. Such work has highlighted how normative expectations of gender, drawn from binarized gender roles, sit at the heart of homophobic and transphobic attitudes. Previous research in high school settings has measured gender and sexuality diverse (GSD) students’ experiences of homo/transphobic harassment as an element of ‘school climate’ with regards to acceptance of gender and sexuality diversity. However, to date, no research has measured GSD students’ perceptions about how valued binarized, gender-normative roles are at their schools, or the ways in which these norms might impact, and potentially constrain, these students’ academic and social schooling lives. The aim of the present study was to address this gap by developing and testing a new, multidimensional measure (the Gender Climate Scale; GCS) of GSD students’ ideas about how gender norms function within their school. Using a convenience sample of 2376 Australian high school students who identify as GSD, the GCS was evaluated for its reliability, construct and criterion validity and measurement invariance using confirmatory factor analysis (CFA) methods. Findings revealed that the estimates produced from the GCS were reliable, valid, and invariant across student reported gender (male/female/non-binary) and location (urban/rural). Criterion validity was supported, with GCS factors representing the promotion of traditional gender roles in the schooling environment negatively associated with perceived school belonging and inclusion and positively associated with bullying and social isolation. Future research with the GCS can inform school and curriculum policy on this important measure of school climate, not just for GSD students but for whole student cohorts.